2021
DOI: 10.3390/biom11111667
|View full text |Cite
|
Sign up to set email alerts
|

Gossypol Acetic Acid Attenuates Cardiac Ischemia/Reperfusion Injury in Rats via an Antiferroptotic Mechanism

Abstract: Myocardial ischemia/reperfusion (I/R) injury has been associated with ferroptosis, which is characterized by an iron-dependent accumulation of lipid peroxide to lethal levels. Gossypol acetic acid (GAA), a natural product taken from the seeds of cotton plants, prevents oxidative stress. However, the effects of GAA on myocardial I/R-induced ferroptosis remain unclear. This study investigated the ability of GAA to attenuate I/R-induced ferroptosis in cardiomyocytes along with the underlying mechanisms in a well-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 33 publications
(49 reference statements)
0
14
0
Order By: Relevance
“…Additionally, the iron-chelating effect of GAA has been confirmed [ 150 ]. It was recently reported that GAA was beneficial in myocardial I/R by protecting cardiomyocytes against ferroptosis and reducing infarct size [ 65 ]. Histochrome (HC) is a water-soluble form of echinochrome A with strong iron-chelating and antioxidant properties [ 151 ].…”
Section: Therapeutic Strategies Targeting Ferroptosis In I/r Injurymentioning
confidence: 99%
“…Additionally, the iron-chelating effect of GAA has been confirmed [ 150 ]. It was recently reported that GAA was beneficial in myocardial I/R by protecting cardiomyocytes against ferroptosis and reducing infarct size [ 65 ]. Histochrome (HC) is a water-soluble form of echinochrome A with strong iron-chelating and antioxidant properties [ 151 ].…”
Section: Therapeutic Strategies Targeting Ferroptosis In I/r Injurymentioning
confidence: 99%
“…Ferroptosis is a new form of cell necrosis mediated by iron-dependent lipid peroxidation [ 10 ]. Ferroptosis has been related to the mechanism associated with lipopolysaccharide-induced cardiac dysfunction and cardiac ischemia/reperfusion injury [ 11 , 12 ]. Although these changes have been observed in acute injury disease models of the heart, it is not clear whether ferroptosis also involved in myocardial damage in DCM.…”
Section: Introductionmentioning
confidence: 99%
“…Icariin (1) ( Liu X. et al, 2021 ), xanthohumol (2) ( Lin et al, 2022 ), britanin (3) ( Lu et al, 2022 ), etomidate (4) ( Lv et al, 2021 ),GAA (5) ( Lin et al, 2021 ),dexmedetomidine (6) ( Wang H. et al, 2022 ), sulforaphane (7) ( Tian Y. et al, 2021 ), naringenin (8) ( Xu et al, 2021 ), C3G (9) ( Shan X. et al, 2021 ), resveratrol (10) ( Xu et al, 2019 ; Li D. et al, 2022 ) , 5-aza-CdR (11) ( Li W. et al, 2021 ), ferulic acid (12) ( Liu XJ. et al, 2021 ), PDA NPs (13) ( Zhang H. et al, 2021 ), atorvastatin (14) ( Peng et al, 2022 ), baicalin (15) ( Fan et al, 2021 ), and ponatinib + deferoxamine (16) ( Tu et al, 2021 ) alleviate ICM through inhibiting ferroptosis ( Table 1 ).…”
Section: Pharmacological Inhibition Of Ferroptosis For Treating Cardi...mentioning
confidence: 99%